Freedom and Democracy or Hunger and Terror: Neoliberalism and Militarization in Latin America - Hristov, Jasmin (Social justice, 2005)
Part of a special issue on the many faces of violence. The writer discusses the coexistence of neoliberalism, militarization, violence, and repression in Colombia, Ecuador, and Mexico since 1990, challenging the notion that democracy is becoming a dominant feature of Latin America's political landscape. She shows how local expressions of global processes conceal class struggle and the pursuit of imperial interests, and she presents evidence of the human costs of the neoliberal agenda.